(untitled) (International Journal of Engineering and Computer Science, 2018)
Location based services are having tremendous growth now a days due to smart phones and tablet devices. To improve the performance of the services several data management concepts have been proposed. Here the Location based service providers are used to provide query services to the users on behalf of the data owners. Sometimes the service can be predicted and fetched according to the user expectation. This will be interrupted due to the lack of service ratings by the users. Sometimes it may result in the incorrect or incomplete service suggestions to the users. This may degrade the performance of the location based services. So, identifying the missing values in the rating before producing the query results is essential for LBS